Pemanfaatan Limbah Bulu Ayam Dan Kulit Singkong Sebagai Bahan Pembuatan Kertas Seni Dengan Penambahan Cao Dan Pewarna Alami - Parnlesta, Sigityawati Aji, Dra. Aminah Asngad, M.Si (2015)
chicken feathers contains crude fiber and skin cassava contains cellulosa, hemicellulosa and lignin, that can be used to make paper. Teak leaf and carica leaf can be used for natural deys. Teak leaf contains of antosianin (to produce red color). Carica leaf contains of chlorofil (green substance leaf) and to produce green color. The purpose of this study to determine the endurance test tensile strenght, tear strenght and sensory test paper art from waste chciken feather and skin cassava with addition of CaO and natural dyes. This study used an experimental method with a completely randomized design (CRD) with two treatment factor is factor 1: comperation of chicken feathers:skin cassava (A) that is A1 (50%:50%), A2 (40%:60%), A3(30%:70%). Factor 2: substance color (B), B1(no color), B2(teak leaf), B3(carica leaf), each treatments was perfomed 2 times repetition. Analysis of the data in the study using qualitative descriptive analysis. The result of the study of art paper highest tensile strenght in treatment A3B2 worth of 6,7080 N, the highest art paper tear strenght on treatment A3B2 worth of 8,0635 N. The results of sensory texture highest in treatment A1B3 worth of 2.65 (rude), the highests color treatment A1B3 worth of 2,90 (dark green), the highest fiber appearance on treatment A2B3 worth of 3,00 (fiber), the highest joy to paper art on treatment A3B3 worth of 2,65 (like). The conclusion of this research there is a difference between tensile strength and tear strength is influenced by differences is composition.